Implementasi Total Quality Management: Prinsip, Strategi, dan Hambatan dalam Peningkatan Mutu Berkelanjutan (Studi Literatur) - Iqbal Maulana; Ummi Sa'adah; Salman Barara; Nuriyah Nuriyah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the fundamental principles, implementation strategies, and challenges encountered in the application of Total Quality Management (TQM) across various organizational contexts. The research employs a qualitative approach based on library research by reviewing key literature from prominent TQM figures such as Deming, Juran, and Crosby, as well as contemporary studies related to quality management. The analysis is conducted through thematic categorization based on the core concepts of TQM, namely customer focus, continuous improvement, data-driven management, and the involvement of all organizational members. The findings indicate that TQM can significantly enhance competitiveness, process efficiency, and service quality when supported by leadership commitment, human resource development, and a strong quality culture. However, its implementation still faces challenges, including resistance to change, limited competencies, unsupportive work culture, and insufficient resources. This study emphasizes that the success of TQM depends not only on managerial techniques but also on cultural transformation and organizational commitment to continuous improvement.